2019
DOI: 10.1002/jcp.27886
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA LINC00483/microRNA‐144 regulates radiosensitivity and epithelial–mesenchymal transition in lung adenocarcinoma by interacting with HOXA10

Abstract: Lung adenocarcinoma (LAD) is the leading cause of cancer death worldwide. Long noncoding RNAs (lncRNAs) have been shown to play an important regulatory role in cancer biology, including that of LAD. The aim of this experiment was to explore the interaction of LINC00483, microRNA‐144 (miR‐144), and homeobox A10 (HOXA10), and their effects on radio sensitivity and epithelial–mesenchymal transition (EMT) of LAD. Initially, microarray analysis was used to screen out miRNAs and lncRNAs, as well as the differentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 39 publications
2
34
0
1
Order By: Relevance
“…It was observed that both miR-144-5p and miR-144-3p had tumor inhibitory effects by targeting several oncogenes in squamous NSCLC including neuronal calcium sensor 1 (NCS1), solute carrier family 44 member 5 (SLC44A5), and myristoylated alanine rich protein kinase C substrate (MARCKS) genes [136]. The upregulation of miR-144 enhances LINC00483 and Homeobox A10 (HOXA10) genes in lung adenocarcinoma, resulting in a tumor suppressor activity through the regulation of EMT [137]. Chen et al indicated that miR-144 negatively controls TIGAR expression and induces apoptosis and autophagy in Lung Cancer [138].…”
Section: Mir-144 In Lung Cancermentioning
confidence: 99%
“…It was observed that both miR-144-5p and miR-144-3p had tumor inhibitory effects by targeting several oncogenes in squamous NSCLC including neuronal calcium sensor 1 (NCS1), solute carrier family 44 member 5 (SLC44A5), and myristoylated alanine rich protein kinase C substrate (MARCKS) genes [136]. The upregulation of miR-144 enhances LINC00483 and Homeobox A10 (HOXA10) genes in lung adenocarcinoma, resulting in a tumor suppressor activity through the regulation of EMT [137]. Chen et al indicated that miR-144 negatively controls TIGAR expression and induces apoptosis and autophagy in Lung Cancer [138].…”
Section: Mir-144 In Lung Cancermentioning
confidence: 99%
“…LncRNAs are abnormally expressed and implicated in regulation of cell processes in gastric cancer [27]. LINC00483 as a novel lncRNA has been reported as key oncogene in human cancers, including gastric cancer [11][12][13]. Previous study has reported that LINC00483 expression was enhanced and promoted gastric cancer cell proliferation via regulating miR-30a-3p and spermassociated antigen 9 (SPAG9) [13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Hu et al reveal that LINC00337 contributes to proliferation of gastric cancer cells by regulating p21 and enhancer of zeste homolog 2 (EZH2) [9]. As for LINC00483, a novel lncRNA, it has been indicated to promote cancer development in endometrial cancer, lung adenocarcinoma and colorectal cancer [10][11][12]. Besides, emerging evidence suggests that LINC00483 could facilitate proliferation, migration and invasion of gastric cancer [13].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, downregulated LINC00483 suppresses tumor cell invasion, migration, and epithelial to mesenchymal transition. It can also bind to miR-144 and encourage the radiosensitivity of LUAD by inhibiting the expression of HOXA10 [22], which promotes LUAD progression directly by enhancing Wnt/β-catenin signaling [23]. Studies suggest that we can improve the clinical radiotherapy effect on LUAD by inhibiting the transcriptional regulation of HOXA10, thus prolonging survival.…”
Section: Discussionmentioning
confidence: 99%